Genre repertoire: the structuring of communicative practices in organizations. - Orlikowski, Wanda J.; Yates, JoAnne (Administrative Science Quarterly, 1994)
In this paper we propose the notions of genre and genre repertoire as analytic tools for investigating the structuring of communicative practices within a community. As organizing structures, genres shape and are shaped by individuals' communicative actions. Our empirical study examined the communication exchanged by a group of distributed knowledge workers in a multiyear, interorganizational project conducted primarily through electronic mail. We found that the genre repertoire of this community revealed a rich and varied array of communicative practices that members shaped and changed in response to community norms, project events, time pressure, and media capabilities. Our analysis establishes the concepts of genre and genre repertoire as a means of understanding communicative action as a central aspect of a community's organizing process. Reprinted by permission of the publisher.